Penerapan Perilaku Hidup Bersih dan Sehat (PHBS) pada Siswa Sanggar Bimbingan Sungai Buloh Selangor Malaysia - Krisna, Krisna Adi Wijaya; Hadiana, Oman; Abdul Manan, Nanan; Astri Nur, Hana; Heriyana, Tio (Lembaga Pengabdian kepada Masyarakat Universitas Langlangbuana, 2024)
Clean and Healthy Living Behavior or PHBS is all attitudes or behaviors towards Health based on awareness that has been carried out so that all members of this family can help themselves in the field. The implementation of this activity aims to provide insight that can help related to the implementation of clean and healthy living behavior and guidance. The method used is first by holding socialization in front of students and teachers when the activity will take place regarding Clean and Healthy Living Behavior (PHBS) such as gymnastics and mutual cooperation, then training for two meetings, then implementation, and finally holding mentoring and evaluation of each activity process from beginning to end at Sanggar Bimbingan (SB) Sungai Buloh, Selangor, Malaysia. Positive things can be obtained after the implementation of this PHBS so that students are not only smart and skilled in knowledge but also strong in physical and mental conditions of children, according to personal researchers this is an important value later when they grow into adults.